Mainstreaming Climate Resilience In Local Land Use Planning: Case Study In Penang Malaysia - Kanasan, Vishanthini A/p (2021)
Cities grow through the mainstreaming of climate resilience, which is an approach linking land use planning and sustainable development goals by integrating climate change information. It also concerns the existing development planning, policies, and decision-making processes. However, a gap exists in the operationalisation of mainstreaming mainly due to the neglect in the institutional reforms required in the approach. Therefore, two key difficulties for mainstreaming climate resilience were emphasised in this research: the lack of sectoral coordination and capacity building between federal, state, and local government. Given the focus by much of the literature on climate change specifically on national-level actions, there is limited knowledge about how the actions should be performed at the local level within the capacity of the local governments as land use planning authority, particularly in Malaysian cities. A multi-method qualitative approach was selected as the researcher aimed to gather multiple forms of data through focus group discussion, semi-structured interview, and in-depth document review into local land-use planning processes and practices in Penang, Malaysia. Local land-use planning in Penang is a “critical case” because it proves the institutional capacity for resilience to climate change for the long term, with the transformational chances for mainstreaming being indicated. The research proposed the framework to offer insights into more practical considerations behind the mainstreaming of climate resilience as an integral part of local land use planning, which involves an interaction between the local context of a city and institutional environment transcending across governance scales